2012
DOI: 10.3748/wjg.v18.i19.2390
|View full text |Cite
|
Sign up to set email alerts
|

A randomized open-label trial of on-demand rabeprazolevsranitidine for patients with non-erosive reflux disease

Abstract: Rabeprazole has a comparable efficacy compared to ranitidine when given on-demand for the treatment of NERD. Both medications were associated with improved quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Correlatively with the literature, in the present study, on-demand treatment with H 2 RA led to a decrease in the complaints of retrosternal burning sensation, regurgitation, nausea, vomiting, and burping. In a study comparing rabeprazole and ranitidine treatments, no significant difference was found between two groups in terms of symptom relief, amount of medication received, and the number of days without medication (23). In the present study, although there was a decrease in the severity of all compliants of GERD in both study groups, only a statistically significant decrease was observed in the H 2 RA group.…”
Section: Discussioncontrasting
confidence: 79%
“…Correlatively with the literature, in the present study, on-demand treatment with H 2 RA led to a decrease in the complaints of retrosternal burning sensation, regurgitation, nausea, vomiting, and burping. In a study comparing rabeprazole and ranitidine treatments, no significant difference was found between two groups in terms of symptom relief, amount of medication received, and the number of days without medication (23). In the present study, although there was a decrease in the severity of all compliants of GERD in both study groups, only a statistically significant decrease was observed in the H 2 RA group.…”
Section: Discussioncontrasting
confidence: 79%
“…However, the use of pharmacological agents comes with the concern of tolerability141516, defined as discontinuation caused for any reason, including ineffectiveness, adverse effects and a lack of compliance. There is substantial evidence for the effectiveness and tolerability of pharmacological agents in the treatment of GERD141718192021. However, most of these findings have been obtained from pairwise comparisons within each class of drugs.…”
mentioning
confidence: 99%
“…One recently published study revealed similar efficacy and degree of improvement in the quality of life assessed with the SF-36 questionnaire in a group of NERD patients given ranitidine or rabeprazole on demand [37].…”
Section: Influence Of Pharmacotherapy On the Quality Of Lifementioning
confidence: 72%